Orchid mycorrhizal and endophytic fungal diversity of three co-occurring terrestrial orchids in the large African genus Disa (Orchidaceae) - Khambule, Nondumiso Venessia (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2020)
Orchids (in the family Orchidaceous) are one of the richest plant families and approximately 500 species are found in South Africa. A number of orchid species are found on disturbed areas and many of the terrestrial species grow in poor soils with low mineral nutrient availability. Most orchid species are thought to be associated with mycorrhizal fungi for germination and mycorrhiza provides nutrients for the survival of adult plants. The aim of this study was to select Orchidaceous plant species and to isolate, identify and characterize the orchid endophytes and assess these isolates for potential antimicrobial and enzymatic activities Isa is the largest genus in South Africa and three Disa species co-occurring in a small geographical area were selected. These included Disa bracteata, D. cornuta and D. polygonoides which span three sections of the genus. Roots were stained to confirm the mycorrhizal status of the Disa species. Mycorrhizal pelotons structures were microscopically observed inside root cells. The presence of pelotons is indictive of mycorrhizal fungal interactions within the orchid roots and areas associated with the site of nutrient exchange between plant and fungus. The presence of pelotons, however, does not give n indication of the fungal species involved. The endophytes were successfully isolated in pure cultures on potato dextrose agar (PDA). All slow growing isolates were selected, and further molecular identification undertaken; DNA was extracted, and PCR amplified using internal transcribed spacer (ITS1F and ITS4) fungal primers. The amplified products were then sequenced and analysed by comparison to sequences in the GenBank database. Trichoderma, Penicillium, Metapochonia, Talaromyces, Oidiodendron Neopestalotiopsis, and Chaetomium were identified from these sequences. The presence of other fungal root endophytes was suspected despite the rigorous surface sterilization procedure used. The primers used to amplify the ITS region are the universal barcoding primers which are specific to fungi. ITS1F is one of the primers designed to amplify a broad range of fungi. DNA was extracted from orchid roots and amplicons were cloned into a pGEMT plasmid vector. Individual clones were sequenced and aligned with Mega software and compared to sequences in the GenBank and UNITE database. Based on percentage sequence identity, unidentified Tulasnella species, Tullasnela colaspora, and various Ascomycota endophytes were identified as contributing to the endophytic root fungal diversity of the selected Disa species. The Disa species investigated in this study were associated with several soil endophytes. D. bracteata, D. polygonoides were collected from the same site along the road verge which is regarded as being disturbed. Based on both culture "“ dependent and independent techniques employed Oidiodendron was found associated with both species. Antimicrobial activity was determined using a well diffusion method using extracts from the isolated fungi against the bacterial isolates Bacillus cereus, Staphylococcus aureus, Escherichia coli and Pseudomonas puptida. Most of the isolated fungi showed at least one potential inhibition effect against one of the bacterial isolates. The extracts that showed potential antimicrobial activity could be further screened to determine the compounds produced as secondary metabolites using techniques such as LC-MS Enzymatic activities of protease, cellulose and amylase were determined using solid media amended with milk protein, carboxymethylcellulose (CMC) and starch. The majority of fungal isolates tested positive with amylase and cellulose with only a few fungal isolates testing positive for protease activity. Broth cultures containing CMC and starch were shown to enhance biomass production in approximately 40 % of the fungal isolates. Degradation of the substrates is required in order to provide carbon to the fungus under test in order to optimize fungal growth as well as to gain insight into their ecological role. Enzyme activity was evident particularly when cellulose and starch were provided as substrates. All the fungal isolates tested grew on the amended medium, with 40% of the isolates preferring to utilize CMC and/or starch, indicating the ability of these fungi to utilize various resources for carbon acquisitions.
Keywords: Orchids -- South Africa; Mycorrhizal fungi -- South Africa; Endomycorrhizas -- South Africa; Endophytes; Orchids Roots